A new protocol to treat moderate to severe intraventricular hemorrhage with obstructive hydrocephalus. (November 2014) - Xia, Chengyu; Cheng, Chuandong; Li, Dongxue; Niu, Chaoshi
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: For patients with intraventricular hemorrhage (IVH) accompanied by obstructive hydrocephalus, external ventricular drainage (EVD) alone is proven to be often insufficient, and lumbar drainage (LD) is proven promising but considered contraindicative in the acute phase. The objective was to analyze the safety and feasibility of treatment for IVH with early continuous LD (CLD) in addition to open EVD regardless of the presence of acute obstructive hydrocephalus. Methods: In this prospective study, 10 consecutive patients with moderate to severe IVH received emergency EVD and early CLD insertion regardless of the presence of obstructive hydrocephalus or blood clots in the third and fourth ventricles. During the whole course of treatment, the EVD was kept open at a safe height until replaced by CLD alone. When the drained CSF from CLD was nearly normal, gradual weaning of the CLD was attempted. Ventriculoperitoneal (VP) shunt would be performed if there was evidence of communicating hydrocephalus. Results: In all the cases, EVD could be safely replaced by CLD alone. There was no evidence of axial herniation or infection, and no requirement of EVD revision. After CLD weaning, only two patients underwent VP shunt procedure. Follow-up study on 3 months and 6 months demonstrated that 7 (70%) patients had good (Glasgow Outcome Scale (GOS) 4 to 5) outcome and 1 (10%) patient died 1 month after discharge due to renal failure. Conclusions: Results suggest that this new therapy which combines EVD with early CLD insertion is safe and easy to manage moderate to severe IVH with obstructive hydrocephalus.